Citizens’ Control as the Form of Preliminary Financial Control - I. G. Lvova (Сибирское юридическое обозрение, 2015)
The article considers the questions of citizens’ control as a part of the preliminary financial control aimed at regulation of budgetary legal relations. This article analyzes the approaches to the concept and content of financial control as the element of public financial resources management which can be found in scientific literature, as well as the need of citizens’ control over the state expenses in order to increase their effectiveness.